MAFLD: Renovation of clinical practice and disease awareness of fatty liver - Kawaguchi, Takumi; Tsutsumi, Tsubasa; Nakano, Dan; Torimura, Takuji (Hepatology research, 2022)
Recently, international expert panels have proposed a new definition of fatty liver: metabolic dysfunction‐associated fatty liver disease (MAFLD). MAFLD is not just a simple renaming of non‐alcoholic fatty liver disease (NAFLD). The unique feature of MAFLD is the inclusion of metabolic dysfunctions, which are high‐risk factors for events. In addition, MAFLD is independent of alcohol intake and the co‐existing causes of liver disease. This new concept of MAFLD may have a widespread impact on patients, medical doctors, medical staff, and various stakeholders regarding fatty liver. Thus, MAFLD may renovate clinical practice and disease awareness of fatty liver. In this review, we introduce the definition of and rationale for MAFLD. We further describe representative cases showing how the diagnostic processes differ between MAFLD and NAFLD. We also summarize recent studies comparing MAFLD with NAFLD and discuss the impact of MAFLD on clinical trials, Japanese populations, and disease awareness.